Kualitas Program Salam TV terhadap Perilaku Generaasi Islami - Andini Nurbahri; M. Amirul Fahmi Srg; Nurhidayah Lubis; Muridayani Muridayani; Arkanuddin Pdg; Maisarah Maisarah (Jutkel: Jurnal Telekomunikasi, Kendali dan Listrik, 2023)
The development of television (television programs) makes other television stations increasingly compete with each other to present the most interesting programs. The packaging of the event is done in such a way with the aim of attracting the hearts of the audience. Currently we watch a lot of TV about religious programs, soap operas and music. As a Muslim millennial generation, we must be smart about using the mass media because the media can play a role in shaping the morale of a nation in the form of information, education and social control in matters of morality and religion. Likewise with a TV station called Salam TV which also doesn't want to miss its programs. One way is to send a religious impression. The main goal is that the Salam TV religious program can provide more interesting Islamic information or learning, so that viewers can agree with the intent or purpose of the program in improving the quality of moral and religious messages through Salam TV stations. This study uses a qualitative method with a case study approach. The results of the study show that the salam tv program can have a big influence on the formation of the religious behavior of the Islamic generation.